The development of generic business models of online retailers - I. S. Pushkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The analysis of templates of the business models which are actively used during an analog era is presented in article and the author's template of a business model of an online retail including the following elements is offered: value for target groups of clients; the products/service made by the company, their quality, functionality, the created additional value; interaction with clients; technological platforms; innovations; services; digital chains of creation of value; the suppliers ready to interact in a digital format; technologies of management; risks. The presented techniques which are used during an analog era have certain shortcomings. On the one hand, they are universal, and with another – do not consider the certain specifics characteristic of business models of a digital era. In particular, there are no such elements as the technological platform and also the technologies used not only for the organization of digital chains of creation of value, but also for further effective digital control. On the basis of the analysis of the existing techniques of creation of business models and key elements of business models of world leaders in the field of production and sales of production the business model template adapted for creation of an online retail in the conditions of digital transformation is offered. The developed template of a business model can be used for start of a startup of the online retail or the translation existing offline business in an online format.